Augmentative Modelling: A Template for Populus sp. Stand Biomass in Eurasia Region - Usoltsev, Vladimir Andreevich; Shobairi, Seyed Omid Reza; Tsepordey, Ivan Stepanovich; Chasovskikh, Viktor Petrovich (Indian Forester, 2021)
Today, estimating of biological productivity or carbon-depositing ability of forests is going on the global level, and its increase is one of the major factors of climate stabilization. In recent years, two trends in the harmonization of allometric models of tree biomass have been developing. The first of them is related to ensuring the additivity of the biomass component composition, and the second one – to the search for the so-called generic model applicable to a wide range of environmental conditions. However, all "generic" models give significant biases in their application in local conditions. In our modeling, we adhere to the principle of biomass additivity, split "generic" model into regional variants by introducing dummy variables, and build the model at the transcontinental level for the first time. When using the unique in terms of the volume of database on the level of stand of the genus Populus sp. in a number of 212 sample plots, the trans-Eurasian additive allometric models of biomass of stands for Eurasian Populus forests are developed, and thereby the combined problem of model additivity and generality is solved. The additive model of forest biomass of Populus is harmonized in two ways: it eliminated the internal contradictions of the component and the total biomass equations, and in addition, it takes into account regional differences of forest stands not only on total, aboveground and underground biomass, but also on its component structure, i.e. it reflects the regional peculiarities of the component structure of biomass.